2.7k views
3 votes
A(c+b)=d solve for the variable c

User Likethesky
by
6.0k points

2 Answers

3 votes

Answer:


c=(d)/(a)-b

Explanation:

a(c + b) = d

Distribute;

ac + ab = d

Subtract AB from both sides;

ac = d - ab

Divide both sides by A


c=(d)/(a)-(ab)/(a)=(d)/(a)-b

User Ichbinblau
by
5.5k points
2 votes

Answer:

c =
(d-ab)/(a)

Explanation:

a(c+b) = d

(expand bracket)

ac + ab = d

(minus ab from both sides)

ac = d - ab

(divide everything by a to get c)

c =
(d-ab)/(a)

User Josh Morrison
by
5.6k points